"Pulsating proptosis and heavy eye syndrome precipitated by neurofibromatosis type 1: A case report". Issue 42 (22nd October 2021) - Lai, Yi-Fen; Lee, Lung-Chi; Chen, Yi-Hao; Chien, Ke-Hung
Abstract : Supplemental Digital Content is available in the text Abstract: Rationale: Neurofibromatosis type 1 (NF1) is a hereditary disease characterized by café-au-lait spots, peripheral neurofibromas, Lisch nodules, optic nerve glioma, and sphenoid wing dysplasia. Pulsating proptosis is associated with a sphenoid bony defect. Heavy eye syndrome is characterized by acquired esohypotropia in patients with high myopia. This study aimed to describe the presentation of pulsating proptosis and heavy eye syndrome precipitated by NF1 and its management. Patient concerns: A 41-year-old woman presented with progressive pulsating proptosis and hypodeviation of the right eye over the past 2 years. The axial length of the right eye was 36.81 mm. The right eye presented with esohypotropia and hypoglobus. The ocular motility examination showed limitations in all directions, especially in supraduction. Brain computed tomography revealed sphenoid wing dysplasia of the right orbit. The meningocele protruded through the orbital defect, lifting the globe. Brain magnetic resonance imaging demonstrated superior rectus muscle (SR) medial displacement and lateral rectus muscle inferior displacement. Physical examination revealed café-au-lait macules and neurofibromas on the trunk. Diagnosis: NF1 with pulsating proptosis and heavy eye syndrome. Interventions: The patient declined neurosurgery due to risk and economic reasons. To manage her main concern regarding cosmetics, we performed orbital floor decompression, SR resection with advancement, maximal hang-back recession of the inferior rectus muscle, and a partial Jensen's procedure. Outcomes: Proptosis was reduced. The eye position became more symmetrical. The range of eye movements was also increased. Lessons: This case describes a rare synchronous presentation of pulsating proptosis and heavy eye syndrome precipitated by NF1. Adult-onset presentation implied a progressive process in NF1. The case also showed a different etiology from that of typical heavy eye syndrome. It reminds ophthalmologists that orbital imaging should be performed in high myopia patients with strabismus to evaluate the extraocular muscle pathway. Furthermore, the case demonstrated a management that avoided the risk and expensive cost of neurosurgery, which has not been reported.